Analysis of the Saintekmu Website Quality on User Satisfaction Using the Modified System Usability Scale and Webqual 4.0 Method - Fitrah, Fitrah Juliansyah; Abdul Fadlil; Rusydi Umar (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
Today, websites are a major means of finding or providing information. The Saintekmu website was created to offer top-notch service to students. One way to ensure that the website's services are appropriate and that information technology is being used to its fullest potential is to evaluate the level of service provided and improve its quality. This study aims to compare the results of two methods - the System Usability Scale (SUS) and Webqual - used to determine the quality and expectations of website users. The study distributed questionnaires online using Google Forms and had a sample size of 20 students. The data collected was analyzed using the SPSS program. The results of the SUS method indicated that the website acceptability range was in the marginal category, with a score of 69.9 and a classification rating of OK. The Webqual method yielded an R square of 0.948, indicating that the website's usability, quality, and interaction variables had a significant effect on user satisfaction. All WebQual 4.0 dimensions had a positive and significant effect on user satisfaction, both partially and simultaneously. This study provides Muhammadiyah Saintek University with reference material to evaluate its website in the future.